Impacts of cooperative membership on rice productivity: Evidence from China - Lin, Bin; Wang, Xiaoxi; Jin, Songqing; Yang, Wanjiang; Li, Houjian (World development, 2022)
•This study combines SFA approach with an ESR model to assess the impact of cooperative membership on rice TFP.•Cooperative membership has positive impacts on rice TFP, TFP growth and its components.•The impacts are highly heterogeneous across regions, farm scales and mechanization levels.•The main impact channels include mechanical cultivation, high-quality seeds and technical training.•Cooperatives should be tailored to meet specific needs of rice producers in a specific region. Productivity growth is essential for food security and sustainable development of agriculture. Since rice is a major staple food in China, understanding factors affecting the performance of rice total factor productivity (TFP) is of great importance for China’s future food security. Despite the growing importance of agricultural TFP, rigorous evidence-based studies on the impacts of cooperative membership on agricultural TFP, especially rice TFP, are scant, hindering the understanding about the potential contribution of agricultural cooperatives to TFP growth. This study examines the impacts of cooperative membership on rice productivity in China by using country-representative survey data from 2014 to 2018. An endogenous switching regression model is employed to account for selection bias. The empirical results show that cooperative membership has a positive and significant impact not only on rice TFP but also on TFP change, technical change and technical efficiency change. The results are robust to alternative choice of instrument variables. The effects of cooperatives on rice productivity are highly heterogeneous with regard to regions, farm scales and mechanization levels. Rice TFP gains through cooperatives are larger for producers in the eastern and central regions, while the effect on TFP growth is the highest in the western region. Regarding farm scales, cooperative membership has a positive and significant impact on rice TFP for small and medium farms but not for large farms. Moreover, cooperatives help improve rice productivity for provinces with low mechanization level of producers. This study further explores the underlying channels through which cooperative membership impacts rice productivity, and identifies that mechanical cultivation, high-quality inputs and technical training appear to be the main channels.